Implementing Process Differentiation Through Tiered Tasks in an ESP Mixed-Ability Classroom - Zurriat Nyndia Rahmawati; Muhammad Rizal Akbar Zamzami (The Study Program of English Education of Palangka Raya University, 2026)
This study examined the implementation of process differentiation through tiered tasks in a mixed-ability English for Specific Purposes (ESP) classroom and explored students' perceptions of the activities. Using a convergent mixed-methods design, the study involved 30 university students in an ESP class in the Islamic Education Department. Data were collected through classroom observations, reflective teaching notes, documentation of students' work, and a questionnaire with closed- and open-ended items. Qualitative data were analyzed thematically, and quantitative data were analyzed using descriptive statistics. The findings showed that process differentiation was implemented through adjusted task responsibilities, scaffolded instructional support, and mixed-ability collaborative roles while maintaining common learning objectives. The qualitative findings indicated that practice-based learning and group collaboration supported students' understanding and participation, whereas language production and group dynamics remained key challenges. Quantitatively, students reported highly positive perceptions, with an overall mean score of 3.36 (Very High). The highest scores were found for Individual Contribution (M = 3.49), Task Integration (M = 3.47), and Group Collaboration (M = 3.46). However, challenges related to pronunciation, speaking performance, communication, and unequal group participation persisted. These findings suggest that tiered tasks offer a practical strategy for implementing differentiated instruction in mixed-ability ESP classrooms, particularly in higher education contexts.